CERPEN ANAK PENYAPU JALAN SEBAGAI MEDIA ALTERNATIF UNTUK IMPLEMENTASI PENGEMBANGAN KARAKTER SISWA (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Abstract As a literary work, short stories have a useful value for the reader. The positive values ​​contained in a short story can be used as an alternative media to develop student character. The objectives of this study were (1) to describe the advantages of short stories from the aspect of the theme, (2) the use of language, (3) background, and (4) moral messages. This research use desciptive qualitative approach. The method used is the method of content analysis (content analysis). The data in this study are the sentences in the short story Anak Sweep Jalan. The instrument used in this study was the classification table. The result of this research is the exposure to the advantages of short stories which is the reason this short story was chosen as an implementation of student character development.